The Automation, Management Control System and Firm Performance – A Conceptual Framework - Alfiandri; Rozita Amiruddin (ADI Publisher, 2020)
Technology evolves therefore, the organizations must keep pace with technological advancements to remain competitive and efficient by automating the system. By implementation of an automation system, work will be effectively and efficiently, reduce cost-effectively and improve the control system. Thus, automation is a formal control that provides rules and standardizations that should be complied with. Implementation of automation would reduce human participation, standardize labour and regulated behaviour in a predictable/programmatic environment. However, it does not necessarily work effectively in a dynamic and flexible environment especially in the manufacturing industry. Drawing on analysis in the field of human-machine interactions in the dynamic environment, management control systems (MCS) provide a nuanced balance between control of standardization and control of flexibility and lead to firm performance. Contingency theory confirms that the function and role of MCS vary according to the context within which firms operate including technology automation. Quantitative methods are used in the study, the data will be collected through the questionnaire. measurement of variables of the study develops from the literature. Unit analysis of the study is the manufacturing industry. The manager of the firm is the respondent of the study. Pre-test will be conducted to ensure the clarity of the questions, minimize error and increase the validity before actual questionnaires are distributed.